Decisão, risco e incerteza: retirada ou reunificação de crianças e jovens em perigo? - Delgado, Paulo (2016)
This study aims to better understand what influences and determines decisions in contexts characterized by complexity and uncertainty, and contributes to the development of recommendations for practice. Based on the work of Davidson-Arad and Benbenishty (2008, 2010), we intended to understand how students from higher education, in scientific areas related to professions involved in decision making processes of children and young people at risk individual care plan, would decide in the presence of a specific case with different scenarios. Participated in the study 200 university students from different regions of Portugal. We used a factorial design (2×2) that involved a questionnaire vignette with four versions. The questionnaire describes the case of a child suspected of being a victim of violence and requires the students to make a decision about the kind of intervention that should be applied in that moment. In addition they must also decide, if the child was removed from her home, whether or not the child should be reunited with the biological family after two years. Among the key findings we highlight the fact that students recognized the risk posed to the child as suffering significant physical and emotional harm. Nevertheless, most decided in favour of an intervention with the biological family, avoiding the removal of the child from their life context. However, in the case of a decision favouring foster care, the majority of the students considered that the child should remain with the foster family when they were asked to reassess the case after two years. It is noted, with statistical significance, that the decision was influenced at first by the agreement or not of the mother to withdrawal and secondly by the child’s desire to be reunited or not with the birth family. We concluded that the development of professional evaluation criteria and decision making should be addressed by including in the curriculum of higher education programmes in the field of child protection, the study of the criteria for the withdrawal, the conditions for the reunification and the advantages of involving the child and the biological family in the intervention.